USING NUMBERED HEADS TOGETHER STRATEGY TO IMPROVE THE READING COMPREHENSION OF THE YEARNINTH STUDENTS OF SMP NEGERI 2 PANGSID SIDRAP REGENCY - Darmawati Darmawati (Publikasi dan UKI Press UKI Toraja., 2020)
English has four skills. one of the them is reading skills. As students, they must face reading in daily life, like in teaching and learning process. In teaching and learning process, the teacher asks the students to read and to do the tasks based on the reading text. For that, the students must have good ability to do the tasks. The fact, some students found difficulties in reading. That’s why, the researcher tried to find a strategy to overcome this problem. One of the strategies that the researcher though can solve this problem is applying the Number Head Together in teaching reading. The purpose of this research is to find out whether the use of Numbered Head Together strategy can improve the students’ reading comprehension. The method used in this research is quasi experimental design. The population of this research is all the students of year ninth of SMP Negeri 2 Pangsid. It consists of six classes and 138 students. The researcher chooses two classes randomly or 46 students as the sample of this research. The result showed that Using Numbered Heads Together Strategy can improve literal comprehension dominantly. The implication of this research refers to all English teachers to use this strategy in teaching reading comprehension. The researcher also suggests to the further researcher to do research on other objectives to support the results of this research.